2017
DOI: 10.3389/fnins.2017.00657
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical and Behavior Deficits in Rats with Iron and Rotenone Co-treatment: Role of Redox Imbalance and Neuroprotection by Biochanin A

Abstract: Increasing evidences show that the etiology of Parkinson's disease (PD) is multifactorial. Studying the combined effect of several factors is becoming a hot topic in PD research. On one hand, iron is one of the essential trace metals for human body; on the other hand, iron may be involved in the etiopathogenesis of PD. In our present study, the rats with increased neonatal iron (120 μg/g bodyweight) supplementation were treated with rotenone (0.5 mg/kg) when they were aged to 14 weeks. We observed that iron an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 69 publications
(86 reference statements)
4
28
0
Order By: Relevance
“…This may be attributed to neuroprotection and less severe damage to dopaminergic neurons among these rats. Similar improvement in dopamine levels postulated to be due to neuroprotective effects of test drugs has been reported after administration of biochanin A (Yu et al, 2017) (in MPTP model), adenosine A receptor blockers (Fathalla et al, 2016) (rotenone model) and catechin (Teixeira et al, 2013) (6-OHDA model). There are many reports concentrating on the dopamine levels in the speci ic regions of the brain and has shown that co-administration of artemisi (Pal and Ghosh, 2018), Juniperus (Bais et al, 2015) and much Chinese herbal preparation (Kum et al, 2011;Pan et al, 2011) resulted in improved dopamine levels.…”
Section: Oxidative Stress Indicatorssupporting
confidence: 74%
“…This may be attributed to neuroprotection and less severe damage to dopaminergic neurons among these rats. Similar improvement in dopamine levels postulated to be due to neuroprotective effects of test drugs has been reported after administration of biochanin A (Yu et al, 2017) (in MPTP model), adenosine A receptor blockers (Fathalla et al, 2016) (rotenone model) and catechin (Teixeira et al, 2013) (6-OHDA model). There are many reports concentrating on the dopamine levels in the speci ic regions of the brain and has shown that co-administration of artemisi (Pal and Ghosh, 2018), Juniperus (Bais et al, 2015) and much Chinese herbal preparation (Kum et al, 2011;Pan et al, 2011) resulted in improved dopamine levels.…”
Section: Oxidative Stress Indicatorssupporting
confidence: 74%
“…The levels of dopamine and its metabolites (DOPAC) in the striatum were measured using an HPLC apparatus (Yu et al, 2017). Briefly, the striatum was weighed and quickly removed on ice.…”
Section: Methodsmentioning
confidence: 99%
“…They tested the co-administration of iron (120 µg/g, intraperitoneally) with rotenone consecutively for 35 days and tested behavioral parameters at 14 weeks. Their cotreated iron plus rotenone group showed worse neurochemical and motor deficits in male and female rats [ 190 ]. Zhang et al (2017) administered rotenone at the dose of 1.5, 2, or 2.5 mg/kg/day for five weeks (in sunflower oil) in male Wistar rats.…”
Section: Neurotoxins Used To Induce Pd In Vivo Modelsmentioning
confidence: 99%